Zinc oxide varistor and preparation method and application thereof

CN122930672APending Publication Date: 2026-10-16STATE GRID HUNAN ELECTRIC COMPANY DISASTER PREVENTION & REDUCTION CENT +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610763956.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-29
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

在特高压输变电、海上风电等极端工况下,电阻片芯片侧面需长期承受高电场、大电流冲击与温度循环作用,传统侧面绝缘层技术已难以满足实际需求

Benefits of technology

[0055]本公开实施例提供的技术方案与现有技术相比具有如下优点:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122930672A_ABST
    Figure CN122930672A_ABST
Patent Text Reader

Abstract

The present disclosure relates to the technical field of zinc oxide resistor disc material preparation, and particularly relates to a zinc oxide resistor disc, a preparation method and application thereof. The zinc oxide resistor disc comprises a resistor disc substrate, an inorganic high-resistance layer arranged on the side surface of the resistor disc substrate, and a glass glaze layer arranged on the outer surface of the inorganic high-resistance layer. The present disclosure solves the technical defects of poor shrinkage compatibility, insufficient insulation strength, limited large-current impact resistance, and easy cracking in thermal cycle of the traditional side surface insulation layer of the zinc oxide resistor disc through the organic combination of formula optimization of the inorganic high-resistance layer, inorganic high-resistance layer-glass glaze layer composite synergy, and nano-scale ZnO doping, and has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to the field of zinc oxide resistor material preparation technology, and in particular to a zinc oxide resistor, its preparation method and application. Background Technology

[0002] Zinc oxide resistors are components used for overvoltage protection in power systems, and are widely used in equipment such as surge arresters, surge protectors, and new energy converters. The performance of their side insulation layer directly determines the operational reliability and service life of the equipment. Under extreme conditions such as ultra-high voltage power transmission and transformation and offshore wind power, the sides of the resistor chip need to withstand high electric fields, large current impacts, and temperature cycling for extended periods. Traditional side insulation layer technology can no longer meet these practical requirements.

[0003] Existing side insulation layer technologies mainly employ single liquid high-resistivity layers, ceramic coatings, or glass glaze coatings, all of which have significant drawbacks: While liquid high-resistivity layers are easy to apply, their components are unevenly dispersed. When glass-forming bodies such as Bi2O3 and Sb2O3 are added directly in powder form, they tend to agglomerate, creating localized weak points in the insulation and increasing side leakage current. Ceramic coatings have mismatched thermal expansion coefficients with the ZnO substrate, easily generating interfacial stress during sintering and cooling, leading to coating cracking and peeling, and consequently, side flashover faults. While single glass glaze coatings can isolate environmental humidity, their adhesion to the substrate is weak, and they are prone to cracking after temperature cycling, making them unsuitable for independently undertaking insulation protection tasks under extreme operating conditions. According to operational data from the Jindongnan UHV substation, from 2021 to 2023, surge arrester maintenance due to resistor side flashover accounted for 40% of the total maintenance frequency, with faults concentrated during periods of frequent thunderstorms and operational shocks, severely impacting the stability of the power grid.

[0004] To address the aforementioned issues, scholars both domestically and internationally have conducted relevant research, but shortcomings remain: some studies have improved the coating's insulation performance by adjusting the amounts of Bi2O3 and SiO2, but have not fully considered the shrinkage matching with the resistor substrate; some studies have explored the regulatory effect of Cr2O3 on the nonlinear coefficient of the resistor, but have not addressed the optimization of the side insulation layer's ability to withstand high current surges.

[0005] Therefore, how to provide a zinc oxide resistance chip that combines high insulation performance and high impact resistance has become an urgent problem to be solved. Summary of the Invention

[0006] To address the aforementioned technical problems, this disclosure provides a zinc oxide resistor sheet, its preparation method, and its application.

[0007] In a first aspect, this disclosure provides a zinc oxide resistive sheet, comprising a resistive sheet substrate, metal electrodes respectively disposed on two end faces of the resistive sheet substrate, an inorganic high-resistivity layer disposed on the side of the resistive sheet substrate, and a glass glaze layer disposed on the outer surface of the inorganic high-resistivity layer. The raw materials for the inorganic high-resistivity layer include inorganic high-resistivity glaze powder and complexing agent; By weight percentage, the inorganic high-resistivity glaze powder comprises 68.9 wt%–76 wt% ZnO, 10.2 wt%–17.1 wt% Sb2O3, 10 wt%–18 wt% SiO2, 2 wt%–3 wt% Bi2O3, 0.5 wt%–1 wt% Co3O4, 0.2 wt%–0.6 wt% Ni2O3, and 0.1 wt%–0.3 wt% Mn3O4; The ZnO includes nano-sized ZnO and micro-sized ZnO, wherein the mass of the nano-sized ZnO is 0.5%-6% of the mass of the micro-sized ZnO; The complexing agent includes a complexing agent capable of forming a chelate with the nano-sized ZnO; The raw materials of the glass glaze layer include SiO2, Al2O3, B2O3, ZnO, MgO and CaO, and the mass ratio of SiO2, Al2O3, B2O3, ZnO, MgO and CaO is (40-60):(5-15):(10-20):(5-15):(2-8):(2-8).

[0008] The ZnO content can be 68.9 wt%, 70 wt%, 72 wt%, 74 wt%, or 76 wt%, etc. The content of Sb2O3 can be 10.2 wt%, 12 wt%, 14 wt%, 16 wt%, or 17.1 wt%, etc.; The SiO2 content can be 10wt%, 12wt%, 14wt%, 16wt%, or 18wt%, etc.; The content of Bi2O3 can be 2wt%, 2.2wt%, 2.4wt%, 2.6wt%, 2.8wt%, or 3wt%, etc.; The content of Co3O4 can be 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, or 1wt%, etc.; The Ni2O3 content can be 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, or 0.6wt%, etc.; The content of Mn3O4 can be 0.1wt%, 0.2wt%, or 0.3wt%, etc.; The mass of nano-sized ZnO is 0.5%, 1%, 2%, 3%, 4%, 5%, or 6% of the mass of micron-sized ZnO, preferably 1-2%. However, this does not limit the values ​​listed above; other values ​​not listed above also apply.

[0009] The mass ratio of SiO2, Al2O3, B2O3, ZnO, MgO and CaO can be 50:10:15:10:7:8, 40:15:20:15:5:5, 60:5:10:9:8:8 or 55:10:20:5:2:8, etc., but is not limited to the values ​​listed above. Other values ​​not listed above are also applicable.

[0010] Regarding the insulation layer system of zinc oxide resistors, this disclosure adopts a synergistic design of inorganic high-resistivity layer and glass glaze to improve the insulation performance and impact resistance of zinc oxide resistors.

[0011] The inorganic high-resistivity layer is primarily composed of ZnO, with SiO2 used to optimize the network structure density, and components such as Bi2O3 and Co3O4 used to improve sintering fluidity. Ni2O3 is used to synergistically regulate the grain boundary barrier distribution and the resistivity of the high-resistivity layer. It preferentially segregates at ZnO grain boundaries to increase the barrier height, suppresses the high-temperature volatilization of Bi2O3, and improves the long-term thermal stability of the coating. Mn3O4, as a variable-valence oxide, regulates the grain boundary carrier concentration, optimizes the nonlinear characteristics of the high-resistivity layer, and simultaneously synergistically forms Zn7Sb2O with Sb2O3. 12 Spinel phase pins grain boundaries, further enhancing the coating's mechanical strength and thermal shock resistance.

[0012] By adding a certain amount of nano-sized ZnO, its size effect can be used to further refine the grains and reduce porosity. During use, it forms chelates with complexing agents to achieve complexation and dispersion, avoiding particle agglomeration and ensuring coating uniformity. However, its content should not be too high, otherwise it will lead to a significant increase in the sintering shrinkage rate of the inorganic high-resistivity layer, a deterioration in the thermal expansion matching with the resistor substrate, and the accumulation of thermal stress at the interface, causing the coating to crack and peel off. At the same time, excessive nano-ZnO will also reduce the overall resistivity of the inorganic high-resistivity layer, reduce the lateral insulation performance, and increase the leakage current. In addition, too many nanoparticles will increase the difficulty of complexation and dispersion, easily forming local agglomeration defects, and the amount of organic residue during the glue removal process will increase the porosity and reduce the density of the coating, ultimately weakening the high-current impact resistance.

[0013] The glass enamel layer uses a SiO2-Al2O3-B2O3 network, where SiO2 acts as the network form, Al2O3 enhances chemical stability, B2O3 lowers the softening temperature, ZnO strengthens the adhesion to the high-resistivity layer, and MgO and CaO synergistically regulate the coefficient of thermal expansion, ensuring thermal compatibility with the inorganic high-resistivity layer and the ZnO matrix. In the glass enamel layer, the ZnO particle size is not less than 200 nm and less than 1 μm.

[0014] Furthermore, based on the synergistic effect of each component, this disclosure further enhances the performance improvement by optimizing their content. Increasing or decreasing the content of any component will affect the overall performance of the resulting high-resistivity layer. For inorganic high-resistivity layers, excessive ZnO content leads to a decrease in the overall resistivity and lateral insulation performance, while insufficient ZnO content results in a large difference between the thermal expansion coefficient and the resistive substrate, causing interfacial stress concentration and making cracking and peeling more likely. Excessive Sb2O3 content leads to excessive precipitation of crystalline phases, disrupting the continuity of the glass network and reducing insulation performance; insufficient Sb2O3 content leads to insufficient interfacial bonding, making the high-resistivity layer prone to detachment during impact. Excessive Bi2O3 content leads to an excessively high proportion of glass phase, decreasing the resistivity of the inorganic high-resistivity layer while increasing the thermal expansion coefficient and worsening the compatibility with the resistive substrate; insufficient Bi2O3 content leads to incomplete melting, discontinuous glass network, increased porosity, and significantly reduced insulation and bonding strength. Excessive SiO2 content leads to a significant increase in the system's melting temperature, insufficient glass phase formation, and decreased bonding strength and impact resistance. Insufficient SiO2 content results in insufficient mechanical strength and poor impact resistance of the inorganic high-resistivity layer, and fails to effectively suppress the high-temperature volatilization of Bi2O3. Excessive Co3O4 content causes a sharp increase in the carrier concentration inside the high-resistivity layer, a significant decrease in overall resistivity, and deterioration of lateral insulation performance. Furthermore, excessive Co ions dissolve in the ZnO lattice, disrupting the stability of the grain boundary Schottky barrier, worsening nonlinear characteristics, lowering the system's sintering temperature, causing abnormal grain growth, reducing coating density, and weakening resistance to high-current impacts. Insufficient Co3O4 content fails to effectively regulate the grain boundary electronic structure, resulting in insufficient grain boundary barrier height, insignificant nonlinear characteristics of the inorganic high-resistivity layer, significantly increased leakage current, and difficulty in suppressing excessive high-temperature diffusion of Bi2O3, leading to uneven grain boundary phase distribution, reduced interfacial bonding strength, and a tendency for delamination during thermal cycling. If the Ni2O3 content is too high, a large number of Ni-rich second phases will form at the grain boundaries, disrupting the continuity of the glass network and reducing the insulation strength of the inorganic high-resistivity layer. Excessive Ni ions will also introduce deep-level defects, increasing the number of carrier recombination centers and making the layer more susceptible to local breakdown under high-current impact. Furthermore, the thermal expansion coefficient of Ni2O3 differs significantly from that of the resistive substrate; excessive addition will increase interfacial thermal stress and the risk of coating cracking. If the Ni2O3 content is too low, it cannot effectively suppress the high-temperature volatilization of Bi2O3, leading to the loss of grain boundary phases during sintering, increased porosity, and decreased coating density and adhesion. Simultaneously, the uneven distribution of grain boundary barriers will worsen the long-term thermal stability of the inorganic high-resistivity layer, and leakage current will tend to increase continuously over time during operation. If the Mn3O4 content is too high, it will lead to the formation of Zn7Sb2O in the system. 12Excessive spinel phase formation disrupts the continuous distribution of the glass phase, increasing the brittleness of the inorganic high-resistivity layer and significantly reducing its mechanical strength and thermal shock resistance. It also makes the layer prone to cracking under temperature cycling or impact loading. Furthermore, excessive variable-valence Mn ions increase grain boundary carrier concentration, leading to a decrease in the resistivity of the inorganic high-resistivity layer and deterioration of its insulation performance. If the Mn3O4 content is too low, it cannot synergistically form sufficient spinel phase with Sb2O3, resulting in insufficient grain boundary pinning, abnormal grain growth, uneven grain size distribution in the coating, and a lack of grain boundary barrier regulation. This leads to poor nonlinear characteristics of the inorganic high-resistivity layer, increased leakage current, and a higher risk of surface flashover under high-current impact.

[0015] For glass glaze layers, if the SiO2 content is too high, the melting temperature of the glass glaze layer will increase significantly, making it difficult for the glaze to fully melt and vitrify. The glaze layer surface will be rough, the porosity will increase, and the density and moisture resistance will decrease significantly. At the same time, the glaze layer will become more brittle, its thermal shock resistance will decrease, and it will be prone to microcracks under temperature cycling. If the SiO2 content is too low, a continuous and complete silicon-oxygen network skeleton cannot be formed, the mechanical strength of the glass glaze layer will be greatly reduced, and its wear resistance and weather resistance will be insufficient. Long-term operation will easily lead to powdering and peeling, and it will not be able to effectively block the intrusion of external moisture, resulting in the deterioration of the insulation performance of the internal high-resistivity layer. If the Al2O3 content is too high, it will significantly increase the melting temperature and viscosity of the glass glaze, resulting in poor glaze fluidity. After sintering, defects such as pinholes and bubbles are likely to occur, and the bonding force between the glaze and the inorganic high-resistivity layer will decrease. At the same time, excessive Al2O3 will precipitate corundum crystal phase, increasing the brittleness of the glaze and making it prone to cracking under impact loads. If the Al2O3 content is too low, the chemical and thermal stability of the glass glaze will be insufficient, making it susceptible to corrosion by acidic and alkaline substances in the atmosphere. Long-term outdoor operation will lead to glaze aging and discoloration, and the thermal shock resistance will deteriorate, making it prone to cracking when the temperature changes suddenly. If the B2O3 content is too high, the coefficient of thermal expansion of the glass glaze will increase sharply, severely deteriorating the thermal compatibility with the inorganic high-resistivity layer and the resistive substrate. This will generate huge interfacial stress during sintering and cooling, causing the glaze to crack and peel off. At the same time, excessive B2O3 will reduce the water resistance of the glaze, making it prone to crystallization and whitening after long-term exposure to moisture, and reducing insulation performance. If the B2O3 content is too low, the fluxing effect will be insufficient, the sintering temperature of the glass glaze will increase, the glaze will not melt sufficiently, and a dense and continuous glaze layer cannot be formed. The porosity will increase, the moisture-proof and insulation performance will be greatly reduced, and the interfacial bonding between the glaze layer and the high-resistivity layer will be insufficient. If the ZnO content is too high, the coefficient of thermal expansion of the glass glaze will increase significantly, widening the thermal expansion difference with the inorganic high-resistivity layer. This leads to stress concentration at the interface, making the glaze layer prone to delamination and peeling. At the same time, excessive ZnO will reduce the insulation resistivity of the glaze layer, decrease the lateral insulation performance, and increase the leakage current. If the ZnO content is too low, the interfacial bonding force between the glass glaze layer and the inorganic high-resistivity layer will be insufficient, and a weak interface will easily form between them. Under high current impact, the glaze layer is prone to peeling, and the coefficient of thermal expansion of the glaze layer cannot be effectively adjusted, resulting in poor thermal matching. If the MgO content is too high, the coefficient of thermal expansion of the glass glaze will be reduced excessively, exacerbating the thermal expansion mismatch with the inorganic high-resistivity layer, generating tensile stress at the interface, and making the glaze prone to cracking after sintering. At the same time, excessive MgO will precipitate brittle crystalline phases such as magnesium olivine, increasing the brittleness of the glaze and significantly reducing its impact resistance. If the MgO content is too low, the coefficient of thermal expansion of the glass glaze cannot be effectively adjusted, resulting in insufficient matching with the inorganic high-resistivity layer and the resistive sheet substrate. Furthermore, the mechanical strength of the glaze will decrease, and its bending and tensile properties will deteriorate.If the CaO content is too high, a large amount of calcium feldspar crystal phase will precipitate in the glass glaze, disrupting the continuity of the glass phase and causing the glaze to become brittle. Under temperature cycling or mechanical impact, it is prone to network cracks. At the same time, excessive CaO will reduce the water resistance of the glaze, and long-term operation will easily lead to alkali return and deterioration of insulation performance. If the CaO content is too low, it will not be able to regulate the coefficient of thermal expansion of the glass glaze, resulting in poor thermal matching with the inorganic high-resistivity layer. Furthermore, the chemical stability of the glaze will decrease, and its corrosion resistance will be weakened.

[0016] The following are preferred technical solutions of this disclosure, but are not intended to limit the technical solutions provided by this disclosure. The technical objectives and beneficial effects of this disclosure can be better achieved through the following technical solutions.

[0017] As a preferred technical solution of this disclosure, the inorganic high-resistivity glaze powder further includes Cr2O3 and / or AlPO4; The content of Cr2O3 by mass percentage does not exceed 6.8 wt%, for example, 0.1 wt%, 1 wt%, 2 wt%, 4 wt% or 6.8 wt%; the content of AlPO4 does not exceed 4.7 wt%, for example, 0.1 wt%, 1 wt%, 2 wt%, 4 wt% or 4.7 wt% or 4.7 wt%, but is not limited to the listed values, and other unlisted values ​​above also apply.

[0018] In this disclosure, the addition of Cr2O3 can refine ZnO grains and increase the number of grain boundaries; AlPO4 can work synergistically with SiO2 to further optimize the dense network structure.

[0019] Preferably, the particle size of the nano-sized ZnO is not less than 200 nm and less than 1 μm, for example, the particle size can be selected as 200 nm, 300 nm, 400 nm, 600 nm or 900 nm, etc.; the particle size of the micron-sized ZnO is 1-5 μm, for example 1 μm, 2 μm, 3 μm, 4 μm or 5 μm, etc., but is not limited to the listed values, and other values ​​not listed above are also applicable.

[0020] As a preferred technical solution of this disclosure, the complexing agent includes citric acid.

[0021] Preferably, the molar ratio of the nano-sized ZnO to the complexing agent is 1:(7-12), such as 1:8, 1:10 or 1:12, but is not limited to the listed values. Other values ​​not listed above are also applicable.

[0022] In this disclosure, an appropriate amount of organic complexing agent helps ensure complete chelation of nano-sized ZnO and achieve uniform dispersion at the elemental level. If too much organic complexing agent is added, it will lead to excessive organic residue during the subsequent debinding process, resulting in increased porosity and decreased density after sintering. If too little organic complexing agent is added, the complexation reaction will be incomplete, and some Bi and Sb elements will still exist in particulate form, which is prone to agglomeration and the formation of local insulation weaknesses.

[0023] As a preferred technical solution of this disclosure, the raw materials of the inorganic high-resistivity layer further include at least one of a dispersant, a defoamer, and a first binder. The added mass of the dispersant is 0.5-1.5 wt% of the total mass of the inorganic high-resistivity glaze powder, for example, 0.5 wt%, 0.8 wt%, 1.0 wt%, 1.2 wt%, or 1.5 wt%. The added mass of the defoamer is 0.1-0.5 wt% of the total mass of the inorganic high-resistivity glaze powder, for example, 0.5 wt%, 0.8 wt%, 1.0 wt%, 1.2 wt%, or 1.5 wt%. The added mass of the first binder is 1.8-4.1 wt% of the total mass of the inorganic high-resistivity glaze powder, for example, 1.8 wt%, 2 wt%, 3 wt%, or 4.1 wt%, but is not limited to the listed values. Other unlisted values ​​mentioned above are also applicable.

[0024] As a preferred technical solution of this disclosure, the raw materials of the glass glaze layer further include a second binder, which includes ethanol, diethylene glycol monobutyl ether (butyl carbitol) and ethyl cellulose. The mixing ratio of the ethanol, the diethylene glycol monobutyl ether and the ethyl cellulose is 100ml:10ml:(2-3)g, for example 100ml:10ml:2g, 100ml:9ml:2.5g, 100ml:8ml:3g or 100ml:10ml:3g, etc., but is not limited to the values ​​listed. Other values ​​not listed above are also applicable.

[0025] As a preferred technical solution of this disclosure, the thickness of the inorganic high-resistivity layer is 0.03-0.12 mm, such as 0.03 mm, 0.05 mm, 0.06 mm, 0.08 mm, 0.1 mm or 0.12 mm; the thickness of the glass enamel layer is 0.25-0.5 mm, such as 0.25 mm, 0.3 mm, 0.35 mm, 0.4 mm or 0.5 mm, but is not limited to the listed values, and other values ​​not listed above are also applicable.

[0026] In this disclosure, a suitable thickness combination can achieve synergistic optimization of the main insulation function and the protection function, taking into account insulation strength, thermal matching, process feasibility and impact resistance reliability, so that the high insulation characteristics of the inorganic high-resistivity layer and the moisture-proof and surface energy dissipation characteristics of the glass glaze layer can be fully utilized. At the same time, the gradient thickness design further alleviates the interfacial thermal stress and improves the long-term stability of the coating under temperature cycling and high current impact.

[0027] If the inorganic high-resistivity layer is too thick, it will increase the temperature difference and shrinkage difference between the inside and outside of the coating during sintering, significantly increasing the accumulated thermal stress inside and making it prone to penetrating microcracks. At the same time, the interfacial shear stress increases linearly with the thickness, greatly increasing the risk of coating delamination and peeling. In addition, an excessively thick coating requires multiple coatings, which not only reduces production efficiency but also easily leads to process defects such as sagging and uneven thickness. It will also increase the overall outer diameter of the resistor element, affecting the internal assembly clearance of the surge arrester and increasing material costs. If the inorganic high-resistivity layer is too thin, it cannot provide sufficient lateral insulation withstand voltage, making it prone to surface breakdown flashover under high electric field. Furthermore, the thin coating has insufficient coverage for minor scratches, protrusions, and other defects on the surface of the resistor element substrate, easily forming local electric field concentration points and causing partial discharge. At the same time, an excessively thin high-resistivity layer cannot prevent the thermal shock generated by the substrate under high current impact from being transmitted outward, which will cause the outer glass enamel layer to crack and fail due to a sudden increase in thermal stress.

[0028] If the glass glaze layer is too thick, it will be difficult for internal air bubbles to escape during the glaze sintering process, increasing porosity and reducing moisture-proof performance. At the same time, the interfacial thermal stress between the glaze layer and the inorganic high-resistivity layer accumulates with increasing thickness, making the glaze surface prone to cracking, blistering, and peeling during cooling. In addition, an excessively thick glaze layer is prone to process defects such as glaze flow and edge accumulation, affecting the dimensional accuracy and appearance consistency of the resistor element, and increasing the overall heat capacity of the coating. Under high current impact, the temperature gradient is aggravated, further deteriorating the thermal matching. If the glass glaze layer is too thin, it cannot form a continuous and dense moisture-proof barrier layer. External moisture can easily penetrate the internal high-resistivity layer through pinholes and micro-gap, causing its insulation resistance to drop sharply and leakage current to increase. Moreover, the surface energy dispersion ability of a thin glaze layer is insufficient, and under high current impact, the electric arc can easily concentrate and burn local areas, directly damaging the inorganic high-resistivity layer. At the same time, an excessively thin glaze layer has poor coverage of micropores and scratches on the surface of the high-resistivity layer, resulting in insufficient weather resistance during long-term outdoor operation, easy powdering and wear, and premature loss of protective function. Furthermore, the thin glaze layer can cause distortion of the surface electric field distribution, with the electric field concentration coefficient at edges and corners increasing by more than 30%. During power frequency operation, it is prone to continuous corona discharge, accelerating glaze aging and carbonization of the inorganic high-resistivity layer surface. Its mechanical wear resistance and impact resistance are significantly reduced. Minor scratches generated during transportation and installation can become the starting point for moisture intrusion and stress concentration. After 3-5 years of operation, dendritic discharge channels along the scratches will appear. Under temperature cycling and multiple lightning thermal shocks, the thin glaze layer lacks sufficient thermal buffering capacity and cannot alleviate the temperature gradient between the inorganic high-resistivity layer and the external environment. The concentration of thermal stress at the interface will induce the rapid propagation of microcracks, eventually leading to large-area flaking of the glaze layer. In Class III and above contamination areas, the surface of the thin glaze layer is more prone to accumulating dirt and forming a conductive film, triggering dry discharge and surface creepage, further eroding the high-resistivity layer, reducing the high-current impact resistance of the resistor and shortening its service life.

[0029] In a second aspect, a method for preparing a zinc oxide resistor sheet as described in the first aspect is provided, comprising: (1) Nano-sized ZnO, a complexing agent and a first solvent are mixed and a complexing reaction is carried out to obtain a complexed dispersion; (2) Micron-sized ZnO, Sb2O3, SiO2, Bi2O3, Co3O4, Ni2O3, and Mn3O4 are mixed with the complexed dispersion liquid described in step (1) to obtain an inorganic high-resistivity layer slurry; (3) The inorganic high-resistivity layer slurry is coated onto the side of the resistor blank, and then subjected to the first heat treatment, the second heat treatment, the third heat treatment and the fourth heat treatment in sequence to form an inorganic high-resistivity layer and obtain a zinc oxide resistor sheet semi-finished product. (4) SiO2, Al2O3, B3O3, ZnO, MgO, CaO and the second binder are mixed to obtain a glass glaze slurry. The glass glaze slurry is coated on the outer surface of the inorganic high-resistivity layer, and then subjected to the fifth heat treatment, the sixth heat treatment and the seventh heat treatment in sequence to form a glass glaze layer. Then, the sheet is ground and aluminum electrodes are sprayed to obtain a zinc oxide resistor sheet.

[0030] It should be noted that the resistor sheet blank is formed into the resistor sheet substrate after a series of heat treatments.

[0031] As a preferred technical solution of this disclosure, in step (1), the first solvent includes ethylene glycol.

[0032] Preferably, the temperature of the complexation reaction in step (1) is 80-95℃, such as 80℃, 85℃, 90℃ or 95℃; the time is 2-3h, such as 2h, 2.2h, 2.4h, 2.6h, 2.8h or 3h, but is not limited to the listed values. Other unlisted values ​​mentioned above are also applicable.

[0033] As a preferred technical solution of this disclosure, the raw materials in step (2) also include at least one of Cr2O3, AlPO4, dispersant, defoamer, and first binder.

[0034] Preferably, the raw materials in step (2) further include a second solvent, which includes water.

[0035] Preferably, the mixing method in step (2) includes intermittent ball milling, which includes: stopping for 10-15 minutes after each 1.8-2.2 hours of ball milling, for a total of 10-12 hours of ball milling. For example, stopping for 10 minutes after each 2 hours of ball milling, for a total of 10 hours of ball milling.

[0036] Preferably, in the inorganic high-resistivity slurry of step (2), the average particle size of the solid particles is ≤2μm, for example, the average particle size is 1μm, 1.2μm, 1.4μm, 1.6μm, 1.8μm or 2μm, etc., but is not limited to the listed values, and other unlisted values ​​are also applicable.

[0037] In this disclosure, limiting the average particle size of the solid particles in the slurry helps to improve the suspension stability and coating uniformity of the slurry, while reducing the porosity after sintering. If the average particle size is too large, it will lead to severe slurry sedimentation, a rough surface after coating, high porosity after sintering, and a significant decrease in insulation and adhesion.

[0038] In this disclosure, the average particle size is measured using laser particle size analysis.

[0039] As a preferred technical solution of this disclosure, step (3) the first stage of heat treatment includes heating to 400-450℃ at a heating rate of 0.5-2.5℃ / min and holding at that temperature for 3-4h; wherein, the heating rate can be 0.5℃ / min, 1℃ / min, 1.5℃ / min or 2.5℃ / min, etc.; the temperature can be 400℃, 420℃ or 450℃, etc.; the time can be 3h, 3.5h or 4h, etc., but is not limited to the values ​​listed above, and other values ​​not listed above are also applicable.

[0040] Preferably, the second heat treatment in step (3) includes heating to 1050-1100℃ at a heating rate of 1-2℃ / min and holding at that temperature for 1.5-2.5h; wherein the heating rate can be 1℃ / min, 1.5℃ / min or 2℃ / min, etc.; the temperature can be 1050℃, 1080℃ or 1100℃, etc.; the time can be 1.5h, 2h or 2.5h, etc., but is not limited to the values ​​listed above, and other values ​​not listed above are also applicable.

[0041] Preferably, the third heat treatment in step (3) includes cooling to 650-750℃ at a cooling rate of 1-2℃ / min; wherein the cooling rate can be 1℃ / min, 1.5℃ / min or 2℃ / min, etc.; the temperature can be 650℃, 700℃ or 750℃, etc., but is not limited to the listed values, and other unlisted values ​​are also applicable.

[0042] Preferably, the fourth stage of heat treatment in step (3) includes cooling to 20-30℃ at a cooling rate of 0.5-2.5℃ / min. The cooling rate can be 0.5℃ / min, 1℃ / min, 1.5℃ / min, or 2.5℃ / min, etc.; the temperature can be 20℃, 25℃, or 30℃, etc., but is not limited to the listed values; other unlisted values ​​are also applicable.

[0043] In this disclosure, a segmented sintering curve was designed to address the difference in thermal properties between the inorganic high-resistivity layer and the zinc oxide resistor substrate, ensuring a tight bond between the high-resistivity layer and the substrate and avoiding interfacial stress caused by excessively rapid heating.

[0044] As a preferred technical solution of this disclosure, after SiO2, Al2O3, B2O3, ZnO, MgO, and CaO are mixed with the second binder in step (4), the solid-liquid ratio is 1g:(1-1.5)mL, such as 1g:1mL, 1g:1.2mL, or 1g:1.5mL, but it is not limited to the values ​​listed above. Other values ​​not listed above are also applicable.

[0045] Preferably, the mixing method in step (4) includes sequential stirring and continuous ball milling, wherein the stirring temperature is 80-90℃ and the time is 2-3h; wherein the stirring temperature can be 80℃, 85℃ or 90℃, etc.; the stirring time can be 2h, 2.5h or 3h, etc., but is not limited to the listed values, and other unlisted values ​​above are also applicable.

[0046] The continuous ball milling speed is 250-350 rpm, and the time is 10-12 h; wherein, the ball milling speed can be 250 rpm, 300 rpm or 350 rpm, etc.; the ball milling time can be 10 h, 11 h or 12 h, etc., but is not limited to the listed values, and other values ​​not listed above are also applicable.

[0047] Preferably, in the glass glaze slurry of step (4), the solid particles have a Dv50 ≤ 1 μm, such as 0.2 μm, 0.4 μm, 0.6 μm, 0.8 μm or 1 μm, but are not limited to the listed values. Other unlisted values ​​mentioned above are also applicable.

[0048] In this disclosure, the glass glaze slurry is subjected to water bath stirring and ball milling processes in sequence to achieve uniform dispersion of components, and the particle size D50 of the solid particles is controlled to ensure coating quality.

[0049] Preferably, the fifth heat treatment in step (4) includes heating to 450-500℃ at a heating rate of 1-3℃ / min and holding at that temperature for 0.5-1h; wherein the heating rate can be 1℃ / min, 2℃ / min or 3℃ / min, etc.; the temperature can be 510℃, 530℃ or 550℃, etc.; the time can be 1h, 1.5h or 2h, etc., but is not limited to the values ​​listed above, and other values ​​not listed above are also applicable.

[0050] Preferably, the sixth heat treatment in step (4) includes heating to 510-550℃ at a heating rate of 1-2℃ / min and holding at that temperature for 1-2 hours; wherein, the cooling rate can be 1℃ / min, 1.5℃ / min or 2℃ / min, etc.; the temperature can be 510℃, 530℃ or 550℃, etc.; the time can be 1 hour, 1.5 hours or 2 hours, etc., but is not limited to the values ​​listed above, and other values ​​not listed above are also applicable.

[0051] Preferably, the seventh heat treatment in step (4) includes cooling to 20-30℃ at a cooling rate of 0.5-1.5℃ / min; wherein the cooling rate can be 0.5℃ / min, 1℃ / min or 1.5℃ / min, etc.; the temperature can be 20℃, 25℃ or 30℃, etc., but is not limited to the listed values, and other unlisted values ​​are also applicable.

[0052] In this disclosure, by controlling the heat treatment process of the glass glaze layer, it is helpful for the interface of the two coatings to fully fuse, so as to give full play to the main insulation function of the inorganic high-resistivity layer and the synergistic effect of the moisture-proof and energy-dispersing effect of the glass glaze layer.

[0053] Furthermore, the preparation method described in this disclosure has the following advantages: In terms of process, no special equipment is required. The heat treatment process of glass glaze layer is compatible with the heat treatment of inorganic high-resistivity layer, and it has a high degree of matching with existing production lines. The performance deviation between different batches is ≤5%, which is suitable for large-scale production. In terms of economic and environmental protection, production costs are reduced by 15%, production efficiency is increased by 20%, and there are no VOC emissions throughout the process, avoiding the pollution problems of organic waste liquid in traditional processes. In terms of application, it has great potential for industrial promotion and can quickly help upgrade power system overvoltage protection equipment.

[0054] Fourthly, this disclosure also provides electrical equipment, including zinc oxide resistor sheets prepared by the preparation method described in the second aspect; The electrical equipment includes surge arresters, surge protectors, or new energy converters.

[0055] The technical solution provided in this disclosure has the following advantages compared with the prior art: This disclosure adopts a two-layer structure of "inorganic high-resistivity layer - glass glaze layer", which realizes the main insulation function of inorganic high-resistivity layer and the synergistic effect of moisture-proof and energy-dispersing effect of glass glaze; furthermore, by optimizing the raw material composition and ratio of the two, its insulation performance and impact resistance are improved. The zinc oxide resistor sheet prepared in this disclosure exhibits a high degree of shrinkage matching between the inorganic high-resistivity layer and the resistor sheet substrate, with a difference in thermal expansion coefficient ≤0.5×10⁻⁶. -6 / K, insulation strength ≥1.1kV / mm, high current impulse withstand capability up to 4 / 10μs100kA, no flashover after 18 2ms square wave impulses, leakage current ≤0.8μA, significantly better than traditional single coating systems. Attached Figure Description

[0056] The accompanying drawings, which are incorporated in and form a part of this specification, illustrate embodiments consistent with this disclosure and, together with the description, serve to explain the principles of this disclosure.

[0057] To more clearly illustrate the technical solutions in the embodiments of this disclosure or the prior art, the accompanying drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0058] Figure 1SEM images of the zinc oxide resistor sheet semi-finished products obtained in Embodiment 1 and Comparative Examples 1-2 of this disclosure; Figure 2 SEM images of zinc oxide resistive sheets prepared in different regions of Embodiment 1 and Comparative Example 1 of this disclosure.

[0059] in, Figure 2 The dashed box in the figure represents the transition region, which is the transition region between the inorganic high-resistivity layer and the resistive substrate. Detailed Implementation

[0060] To better understand the above-mentioned objectives, features, and advantages of this disclosure, the solutions disclosed herein will be further described below. It should be noted that, unless otherwise specified, the embodiments and features described herein can be combined with each other.

[0061] Numerous specific details are set forth in the following description in order to provide a full understanding of this disclosure, but this disclosure may also be implemented in other ways different from those described herein; obviously, the embodiments in the specification are only some, and not all, of the embodiments of this disclosure.

[0062] Unless otherwise specified, all raw materials involved in this embodiment are commercially available analytical grade reagents; unless otherwise specified, all instruments and equipment involved are conventional laboratory or industrial production equipment.

[0063] The agate grinding balls were purchased from Changsha Miqi Instrument Equipment Co., Ltd., and the diameter of each grinding ball is 3-10mm. The planetary ball mill selected is model XLXPM-100 from Wuhan Hengle Machinery Equipment Co., Ltd. The air spray gun used is the WIDER1A-10E2PAC model from Anastar Iwata Corporation. The resistor blank (i.e., zinc oxide resistor blank) is selected from Hunan Gaoxin Fu'an Electric Technology Co., Ltd., item number: GXFA-D42.

[0064] Example 1 This embodiment provides a zinc oxide resistor sheet and its preparation method. The zinc oxide resistor sheet includes a resistor sheet substrate, aluminum electrodes respectively disposed on two end faces of the resistor sheet substrate, an inorganic high-resistivity layer (0.06 mm) disposed on the side of the resistor sheet substrate, and a glass glaze layer (0.3 mm) disposed on the outer surface of the inorganic high-resistivity layer. The raw materials for the inorganic high-resistance layer include inorganic high-resistance glaze powder, complexing agent, dispersant, defoamer, and first binder; By weight percentage, the inorganic high-resistivity glaze powder comprises 68.9 wt% ZnO, 13.7 wt% Sb2O3, 10 wt% SiO2, 2.5 wt% Bi2O3, 0.9 wt% Co3O4, 0.4 wt% Ni2O3, 0.2 wt% Mn3O4 and 3.4 wt% Cr2O3; The ZnO includes nano-sized ZnO (particle size 50 nm) and micro-sized ZnO (particle size 5 μm), wherein the mass of the nano-sized ZnO is 1% of the mass of the micro-sized ZnO; The complexing agent is citric acid, and the molar ratio of nano-sized ZnO to citric acid is 1:8; The dispersant is polymethacrylamide, and the added mass of the dispersant is 0.75% of the total mass of the inorganic high-resistance glaze powder. The defoamer is tributyl phosphate, and the added mass of the defoamer is 0.25% of the total mass of the inorganic high-resistance glaze powder. The first binder is polyvinyl alcohol (PVA), and the added mass of the first binder is 4% of the total mass of the inorganic high-resistivity glaze powder; The raw materials of the glass glaze layer include SiO2, Al2O3, B2O3, ZnO, MgO, CaO and a second binder, and the mass ratio of SiO2, Al2O3, B2O3, ZnO, MgO and CaO is 50:10:15:10:5:5. The second binder is a combination of ethanol, diethylene glycol monobutyl ether (butyl carbitol) and ethyl cellulose, wherein the mixing ratio of ethanol, diethylene glycol monobutyl ether and ethyl cellulose is 100ml:8ml:2.5g.

[0065] The preparation method includes: (1) Citric acid and 13.8g of nano-sized ZnO were dissolved in ethylene glycol and stirred at 90°C for 3h to form a complex dispersion; (2) Mix 1364.2g of micron-sized ZnO, 273.6g of Sb2O3, 200g of SiO2, 50g of Bi2O3, 18g of Co3O4, 8g of Ni2O3, 4g of Mn3O4, 68.4g of Cr2O3, 15g of dispersant, 5g of defoamer, 80g of the first binder and the complexed dispersion, and add deionized water to adjust the solid-liquid ratio to 1g:3mL; transfer to a star ball mill for intermittent ball milling, that is, at a speed of 400rpm, stop for 10min every 2h of ball milling, and accumulate ball milling for 10h to obtain an inorganic high-resistance layer slurry with an average particle size of 1.8μm; (3) Prepare a resistor blank with a diameter of 42mm and a thickness of 25mm. Coat the side of the resistor blank with the inorganic high resistance layer slurry. After drying at 80℃ for 45min, perform the first heat treatment, the second heat treatment, the third heat treatment and the fourth heat treatment in sequence to form an inorganic high resistance layer and obtain a zinc oxide resistor blank semi-finished product. The first stage of heat treatment involves heating to 430℃ at a rate of 1℃ / min and holding at that temperature for 2 hours. Second stage of heat treatment: Heat to 1050℃ at a heating rate of 1.5℃ / min and hold for 3.5h; The third stage of heat treatment: cooling to 700℃ at a cooling rate of 1℃ / min; Fourth stage heat treatment: Cool down to 22℃ at a cooling rate of 3℃ / min; (4) SiO2, Al2O3, B2O3, ZnO, MgO, CaO and the second binder are mixed and the solid-liquid ratio is controlled at 1g:1.2mL. The mixture is stirred in a water bath at 85℃ for 3h, left to stand for 24h, and after defoaming, it is transferred to a planetary ball mill and ball-milled at 300rpm for 12h to obtain a glass glaze slurry with a solid particle size D50 of 0.8μm. The glass glaze slurry is sprayed onto the outer surface of the inorganic high-resistivity layer at a pressure of 0.3MPa and a distance of 15cm, and the thickness is controlled at 0.3mm. Then, the fifth heat treatment, the sixth heat treatment and the seventh heat treatment are performed in sequence to form a glass glaze layer. Then, the sheet is ground and aluminum electrode is sprayed to obtain a zinc oxide resistor sheet. The fifth stage of heat treatment involves heating to 480℃ at a rate of 2℃ / min and holding at that temperature for 0.5 hours. Sixth stage heat treatment: Heat to 510℃ at a heating rate of 1℃ / min and hold for 1 hour; Seventh stage heat treatment: Cool down to 25℃ at a cooling rate of 1℃ / min.

[0066] Example 2 This embodiment provides a zinc oxide resistor sheet and its preparation method. The zinc oxide resistor sheet includes a resistor sheet substrate, aluminum electrodes respectively disposed on two end faces of the resistor sheet substrate, an inorganic high-resistivity layer (0.04 mm) disposed on the side of the resistor sheet substrate, and a glass glaze layer (0.4 mm) disposed on the outer surface of the inorganic high-resistivity layer. The raw materials for the inorganic high-resistance layer include inorganic high-resistance glaze powder, complexing agent, dispersant, defoamer, and first binder; By weight percentage, the inorganic high-resistivity glaze powder comprises 76 wt% ZnO, 10.2 wt% Sb2O3, 10 wt% SiO2, 2 wt% Bi2O3, 0.5 wt% Co3O4, 0.2 wt% Ni2O3, 0.1 wt% Mn3O4, 0.5 wt% Cr2O3 and 0.5 wt% AlPO4; The ZnO includes nano-sized ZnO (particle size 50 nm) and micro-sized ZnO (particle size 5 μm), wherein the mass of the nano-sized ZnO is 6% of the mass of the micro-sized ZnO; The complexing agent is citric acid, and the molar ratio of nano-sized ZnO to citric acid is 1:12; The dispersant is polymethacrylamide, and the added mass of the dispersant is 1% of the total mass of the inorganic high-resistivity glaze powder. The defoamer is tributyl phosphate, and the added mass of the defoamer is 0.3% of the total mass of the inorganic high-resistance glaze powder. The first binder is polyvinyl alcohol (PVA), and the added mass of the first binder is 3% of the total mass of the inorganic high-resistivity glaze powder; The raw materials of the glass glaze layer include SiO2, Al2O3, B2O3, ZnO, MgO, CaO and a second binder, and the mass ratio of SiO2, Al2O3, B2O3, ZnO, MgO and CaO is 60:5:20:15:2:8. The second binder is a combination of ethanol, diethylene glycol monobutyl ether (butyl carbitol) and ethyl cellulose, wherein the mixing ratio of ethanol, diethylene glycol monobutyl ether and ethyl cellulose is 100ml:8ml:2.5g.

[0067] The preparation method includes: (1) Citric acid and 91.2g of nano-sized ZnO were dissolved in ethylene glycol and stirred at 85°C for 3h to form a complex dispersion. (2) Mix 1428.8g of micron-sized ZnO, 204g of Sb2O3, 200g of SiO2, 40g of Bi2O3, 10g of Co3O4, 4g of Ni2O3, 2g of Mn3O4, 10g of Cr2O3, 10g of AlPO4, 20g of dispersant, 6g of defoamer, 60g of first binder and the complexed dispersion, and add deionized water to adjust the solid-liquid ratio to 1g:3mL; transfer to a star ball mill for intermittent ball milling, that is, at a speed of 400rpm, stop for 10min every 2.2h of ball milling, and accumulate ball milling for 12h to obtain an inorganic high-resistivity layer slurry with an average particle size of 1.6μm; (3) Prepare a resistor blank with a diameter of 42mm and a thickness of 25mm. Coat the side of the resistor blank with the inorganic high resistance layer slurry. After drying at 80℃ for 45min, perform the first heat treatment, the second heat treatment, the third heat treatment and the fourth heat treatment in sequence to form an inorganic high resistance layer and obtain a zinc oxide resistor blank semi-finished product. The first stage of heat treatment involves heating to 450℃ at a rate of 1℃ / min and holding at that temperature for 2 hours. Second stage of heat treatment: Heat to 1100℃ at a heating rate of 1.5℃ / min and hold for 3.5h; The third stage of heat treatment: cooling to 730℃ at a cooling rate of 1℃ / min; Fourth stage heat treatment: Cool down to 22℃ at a cooling rate of 3℃ / min; (4) SiO2, Al2O3, B2O3, ZnO, MgO, CaO and the second binder are mixed and the solid-liquid ratio is controlled at 1g:1.2mL. The mixture is stirred in a water bath at 85℃ for 3h, and then left to stand for 24h. After defoaming, it is transferred to a planetary ball mill and ball-milled at 350rpm for 10h to obtain a glass glaze slurry with a solid particle size D50 of 0.9μm. The glass glaze slurry is sprayed onto the outer surface of the inorganic high-resistivity layer at a pressure of 0.3MPa and a distance of 15cm, and the thickness is controlled at 0.4mm. Then, the fifth, sixth and seventh heat treatments are performed in sequence to form a glass glaze layer. Then, the sheet is ground and aluminum electrodes are sprayed to obtain a zinc oxide resistor sheet. The fifth stage of heat treatment involves heating to 450℃ at a rate of 2℃ / min and holding at that temperature for 0.7 hours. Sixth stage heat treatment: Heat to 520℃ at a heating rate of 1℃ / min and hold for 1 hour; Seventh stage heat treatment: Cool down to 25℃ at a cooling rate of 1℃ / min.

[0068] Example 3 This embodiment provides a zinc oxide resistor sheet and its preparation method. The zinc oxide resistor sheet includes a resistor sheet substrate, aluminum electrodes respectively disposed on two end faces of the resistor sheet substrate, an inorganic high-resistivity layer (0.08 mm) disposed on the side of the resistor sheet substrate, and a glass glaze layer (0.25 mm) disposed on the outer surface of the inorganic high-resistivity layer. The raw materials for the inorganic high-resistance layer include inorganic high-resistance glaze powder, complexing agent, dispersant, defoamer, and first binder; The inorganic high-resistivity glaze powder comprises, by weight percentage, 70 wt% ZnO, 10.2 wt% Sb2O3, 11.8 wt% SiO2, 3 wt% Bi2O3, 1 wt% Co3O4, 0.6 wt% Ni2O3, 0.3 wt% Mn3O4 and 3.1 wt% Cr2O3; The ZnO includes nano-sized ZnO (50nm particle size) and micro-sized ZnO (5μm), and the mass of the nano-sized ZnO is 4% of the mass of the micro-sized ZnO. The complexing agent is citric acid, and the molar ratio of nano-sized ZnO to citric acid is 1:7; The dispersant is polymethacrylamide, and the added mass of the dispersant is 1% of the total mass of the inorganic high-resistivity glaze powder. The defoamer is tributyl phosphate, and the added mass of the defoamer is 0.2% of the total mass of the inorganic high-resistance glaze powder. The first binder is polyvinyl alcohol (PVA), and the added mass of the first binder is 2% of the total mass of the inorganic high-resistivity glaze powder; The raw materials of the glass glaze layer include SiO2, Al2O3, B2O3, ZnO, MgO, CaO and a second binder, and the mass ratio of SiO2, Al2O3, B2O3, ZnO, MgO and CaO is 40:15:10:5:8:8. The second binder is a combination of ethanol, diethylene glycol monobutyl ether (butyl carbitol) and ethyl cellulose, wherein the mixing ratio of ethanol, diethylene glycol monobutyl ether and ethyl cellulose is 100ml:8ml:2.5g.

[0069] The preparation method includes: (1) Dissolve citric acid and 7g of nano-sized ZnO in ethylene glycol and stir at 90°C for 3h to form a complex dispersion; (2) Mix 1393g of micron-sized ZnO, 204g of Sb2O3, 236g of SiO2, 60g of Bi2O3, 20g of Co3O4, 12g of Ni2O3, 3g of Mn3O4, 62g of Cr2O3, 20g of dispersant, 4g of defoamer, 80g of the first binder and the complexed dispersion, and add deionized water to adjust the solid-liquid ratio to 1g:3mL; transfer to a star ball mill for intermittent ball milling, that is, at a speed of 400rpm, stop for 10min every 2h of ball milling, and accumulate ball milling for 10h to obtain an inorganic high-resistivity layer slurry with an average particle size of 1.6μm; (3) Prepare a resistor blank with a diameter of 42mm and a thickness of 25mm. Coat the side of the resistor blank with the inorganic high resistance layer slurry. After drying at 80℃ for 45min, perform the first heat treatment, the second heat treatment, the third heat treatment and the fourth heat treatment in sequence to form an inorganic high resistance layer and obtain a zinc oxide resistor blank semi-finished product. The first stage of heat treatment involves heating to 400℃ at a rate of 1℃ / min and holding at that temperature for 4 hours. Second stage of heat treatment: Heat to 1080℃ at a heating rate of 1.5℃ / min and hold for 2.5h; The third stage of heat treatment: cooling to 690℃ at a cooling rate of 1℃ / min; Fourth stage heat treatment: Cool down to 25℃ at a cooling rate of 3℃ / min; (4) SiO2, Al2O3, B2O3, ZnO, MgO, CaO and the second binder are mixed and the solid-liquid ratio is controlled at 1g:1.2mL. The mixture is stirred in a water bath at 85℃ for 3.5h and allowed to stand for 24h. After defoaming, it is transferred to a planetary ball mill and ball-milled at 300rpm for 12h to obtain a glass glaze slurry with a solid particle size D50 of 0.6μm. The glass glaze slurry is sprayed onto the outer surface of the inorganic high-resistivity layer at a pressure of 0.3MPa and a distance of 15cm, and the thickness is controlled at 0.25mm. Then, the fifth, sixth and seventh heat treatments are performed in sequence to form a glass glaze layer. The sheet is then ground and aluminum electrodes are sprayed to obtain a zinc oxide resistor sheet. The fifth stage of heat treatment involves heating to 500℃ at a rate of 2℃ / min and holding at that temperature for 0.5 hours. The sixth stage of heat treatment: heat to 550℃ at a heating rate of 1℃ / min and hold for 1.5h; Seventh stage heat treatment: Cool down to 25℃ at a cooling rate of 1℃ / min.

[0070] Comparative Example 1 This comparative example provides a zinc oxide resistor sheet and its preparation method. The zinc oxide resistor sheet is the same as the zinc oxide resistor sheet in Example 1, except that the inorganic high-resistivity glaze powder does not contain nano-sized ZnO, and the missing mass is made up by micron-sized ZnO.

[0071] The preparation method is the same as that in Example 1, except that; There is no operation in step (1); Furthermore, step (3) becomes: prepare a resistor blank with a diameter of 42 mm and a thickness of 25 mm, coat the inorganic high-resistivity layer slurry on the side of the resistor blank, dry it at 80°C for 45 min, then heat it to 1050°C at a heating rate of 1.5°C / min, keep it at that temperature for 3.5 h, and then cool it to 22°C at a cooling rate of 3°C / min.

[0072] Comparative Example 2 This comparative example provides a zinc oxide resistor sheet and its preparation method. The zinc oxide resistor sheet is the same as the zinc oxide resistor sheet in Example 1, except that a glass glaze layer is not provided.

[0073] The preparation method is the same as that in Example 1, except that no operations related to the coating of glass glaze are performed in step (4).

[0074] Comparative Example 3 This comparative example provides a zinc oxide resistor sheet and its preparation method. The zinc oxide resistor sheet is the same as the zinc oxide resistor sheet in Example 1, except that the inorganic high-resistivity glaze powder does not contain nano-sized ZnO, and the missing mass is made up by micron-sized ZnO.

[0075] The preparation method is the same as that in Example 1, except that step (1) is omitted.

[0076] Performance testing (a) The zinc oxide resistors prepared in Example 1 and Comparative Examples 1-2 were characterized.

[0077] The SEM images of the zinc oxide resistor sheet semi-finished products obtained in Example 1 and Comparative Examples 1-2 are shown below. Figure 1 As shown; SEM images of zinc oxide resistive sheets prepared in Example 1 and Comparative Example 1 in different regions are shown below. Figure 2 As shown.

[0078] Depend on Figure 1 It can be seen that the inorganic high-resistivity layer obtained in Example 1 has a smooth and dense surface without obvious pores and cracks, and the coating is uniform and tightly bonded to the substrate; Comparative Example 1 and Comparative Example 2 both show obvious pores, local roughness and even microcracks, and the structural uniformity and density are significantly worse than those of Example 1.

[0079] Depend on Figure 2 It can be seen that in Example 1, there is a continuous and uniform transition zone between the inorganic high-resistivity layer and the resistive substrate, the interface is firmly bonded, there is no delamination or gaps, and the grains are evenly distributed; in Comparative Example 1, the interface transition zone is not obvious, there are obvious interface gaps, the local bonding is poor, and it is easy to cause interface debonding and surface flashover.

[0080] (II) The zinc oxide resistive sheets prepared in Example 1 and Comparative Examples 1-2 were tested according to GB / T11032-2020 standard. Five samples were tested in each group, and the average value of the results was taken. The test indicators included: insulation strength, difference in thermal expansion coefficient (resistive sheet substrate and inorganic high-resistivity layer), high current impulse withstand performance (4 / 10μs), number of 2ms square wave impulses, and 0.75U 1mA Leakage current; Among them, the thermal expansion tester of DIL402 was used to test the thermal expansion of the resistive sheet substrate and the inorganic high-resistivity layer respectively, and the thermal expansion coefficient was obtained. The difference in thermal expansion coefficient = thermal expansion coefficient of resistive sheet substrate - thermal expansion coefficient of inorganic high-resistivity layer.

[0081] The test results are shown in Table 1.

[0082] Table 1

[0083] As shown in Table 1, the zinc oxide resistor sheet prepared in the embodiments of this disclosure is significantly better than Comparative Example 1 and Comparative Example 2 in all performance indicators.

[0084] In Example 1, the insulation strength reached 1.2 kV / mm, a 50% improvement compared to Comparative Example 1 and a 20% improvement compared to Comparative Example 2, effectively solving the defect of weak insulation in traditional side insulation layers. The high-current surge withstand performance reached 100 kA, a 66.7% improvement compared to Comparative Example 1 and a 25% improvement compared to Comparative Example 2, capable of handling extreme current surges in scenarios such as ultra-high voltage and offshore wind power. The leakage current was controlled at 0.8 μA, a 68% reduction compared to Comparative Example 1 and a 46.7% reduction compared to Comparative Example 2, significantly improving the operational stability of the resistor and reducing energy consumption and aging losses. Meanwhile, the difference in the coefficient of thermal expansion between Example 1 and Example 2 was only 0.4 × 10⁻⁶. -6 The 2ms square wave impact of / K and 18 times without flashover further proves the comprehensive advantages of the zinc oxide resistor provided in this disclosure in terms of structural matching, anti-aging and anti-flashover capability.

[0085] This disclosure systematically solves the technical defects of traditional zinc oxide resistor sheets, such as poor shrinkage compatibility of the side insulation layer, insufficient insulation strength, limited high-current impact resistance, and easy cracking during thermal cycling, through the organic integration of inorganic high-resistivity layer formulation optimization, inorganic high-resistivity layer-glass glaze layer composite synergy, and nano-level ZnO doping, combined with segmented temperature-controlled sintering. The prepared zinc oxide resistor sheet not only has excellent side insulation layer performance, strong structural stability, and outstanding impact resistance, but the manufacturing process does not require additional special equipment, is highly compatible with existing production lines, and can directly achieve large-scale mass production. Compared with traditional processes, the production cost is reduced by 15%, the production efficiency is increased by 20%, and there are no VOC emissions throughout the process, balancing economic efficiency and environmental protection, and conforming to the industrial development trend of green manufacturing. This resistor sheet can be widely adapted to various extreme operating conditions such as ultra-high voltage power transmission and transformation equipment, offshore wind power surge arresters, and new energy converters, effectively ensuring the long-term stable operation of power equipment in complex environments such as high humidity, strong impact, and severe temperature cycling. It has broad market application prospects and extremely high industrialization value and social benefits.

[0086] It should be noted that, in this document, relational terms such as "first" and "second" are used merely to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitations, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element.

[0087] The above description is merely a specific embodiment of this disclosure, enabling those skilled in the art to understand or implement it. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of this disclosure. Therefore, this disclosure is not to be limited to the embodiments described herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A zinc oxide resistor, characterized in that, It includes a resistive sheet substrate, metal electrodes respectively disposed on two end faces of the resistive sheet substrate, an inorganic high-resistivity layer disposed on the side of the resistive sheet substrate, and a glass glaze layer disposed on the outer surface of the inorganic high-resistivity layer. The raw materials for the inorganic high-resistivity layer include inorganic high-resistivity glaze powder and complexing agent; By weight percentage, the inorganic high-resistivity glaze powder comprises 68.9 wt% – 76 wt% ZnO, 10.2 wt% – 17.1 wt% Sb2O3, 10 wt% – 18 wt% SiO2, 2 wt% – 3 wt% Bi2O3, 0.5 wt% – 1 wt% Co3O4, 0.2 wt% – 0.6 wt% Ni2O3, and 0.1 wt% – 0.3 wt% Mn3O4; The ZnO includes nano-sized ZnO and micro-sized ZnO, wherein the mass of the nano-sized ZnO is 0.5%-6% of the mass of the micro-sized ZnO; The complexing agent includes a complexing agent capable of forming a chelate with the nano-sized ZnO; The raw materials of the glass glaze layer include SiO2, Al2O3, B2O3, ZnO, MgO and CaO, and the mass ratio of SiO2, Al2O3, B2O3, ZnO, MgO and CaO is (40-60):(5-15):(10-20):(5-15):(2-8):(2-8).

2. The zinc oxide resistor sheet according to claim 1, characterized in that, The inorganic high-resistivity glaze powder also includes Cr2O3 and / or AlPO4; The content of Cr2O3 by mass percentage does not exceed 6.8 wt%, and the content of AlPO4 does not exceed 4.7 wt%. Preferably, the particle size of the nano-sized ZnO is not less than 200 nm and less than 1 μm, and the particle size of the micron-sized ZnO is 1-5 μm.

3. The zinc oxide resistor sheet according to claim 1 or 2, characterized in that, The complexing agent includes citric acid; Preferably, the molar ratio of the nano-sized ZnO to the complexing agent is 1:(7-12).

4. The zinc oxide resistor sheet according to any one of claims 1-3, characterized in that, The raw materials for the inorganic high-resistance layer also include at least one of a dispersant, a defoamer, and a first binder. The added mass of the dispersant is 0.5-1.5 wt% of the total mass of the inorganic high-resistance glaze powder, the added mass of the defoamer is 0.1-0.5 wt% of the total mass of the inorganic high-resistance glaze powder, and the added mass of the first binder is 1.8-4.1 wt% of the total mass of the inorganic high-resistance glaze powder. Preferably, the raw materials of the glass glaze layer further include a second binder, which includes ethanol, diethylene glycol monobutyl ether and ethyl cellulose, wherein the mixing ratio of ethanol, diethylene glycol monobutyl ether and ethyl cellulose is 100ml:(8-10ml):(2-3)g.

5. The zinc oxide resistor sheet according to any one of claims 1-4, characterized in that, The thickness of the inorganic high-resistivity layer is 0.03-0.12 mm, and the thickness of the glass glaze layer is 0.25-0.5 mm.

6. A method for preparing a zinc oxide resistor sheet as described in any one of claims 1-5, characterized in that, include: (1) Nano-sized ZnO, complexing agent and first solvent are mixed and complexed to obtain complexed dispersion; (2) Micron-sized ZnO, Sb2O3, SiO2, Bi2O3, Co3O4, Ni2O3, Mn3O4 are mixed with the complexed dispersion liquid described in step (1) to obtain an inorganic high-resistivity slurry; (3) The inorganic high-resistivity layer slurry is coated onto the side of the resistor blank, and then subjected to the first heat treatment, the second heat treatment, the third heat treatment and the fourth heat treatment in sequence to form an inorganic high-resistivity layer and obtain a zinc oxide resistor sheet semi-finished product. (4) SiO2, Al2O3, B2O3, ZnO, MgO, CaO and the second binder are mixed to obtain a glass glaze slurry. The glass glaze slurry is coated on the outer surface of the inorganic high-resistivity layer, and then subjected to the fifth heat treatment, the sixth heat treatment and the seventh heat treatment in sequence to form a glass glaze layer. Then, the sheet is ground and aluminum electrodes are sprayed to obtain a zinc oxide resistor sheet.

7. The preparation method according to claim 6, characterized in that, Step (1) The first solvent includes ethylene glycol; Preferably, the temperature of the complexation reaction in step (1) is 80-95℃ and the time is 2-3h; Preferably, the raw materials in step (2) further include at least one of Cr2O3, AlPO4, dispersant, defoamer, and first binder; Preferably, the raw materials in step (2) further include a second solvent, which includes water; preferably, the mixing method in step (2) includes intermittent ball milling, which includes stopping for 10-15 minutes every 1.8-2.2 hours of ball milling, for a total of 10-12 hours of ball milling. Preferably, in the inorganic high-resistivity slurry of step (2), the average particle size of the solid particles is ≤2μm.

8. The preparation method according to claim 6 or 7, characterized in that, Step (3) The first heat treatment includes heating to 400-450℃ at a heating rate of 0.5-2.5℃ / min and holding at that temperature for 3-4 hours; Preferably, the second heat treatment in step (3) includes heating to 1050-1100℃ at a heating rate of 1-2℃ / min and holding at that temperature for 1.5-2.5h; Preferably, the third stage of heat treatment in step (3) includes cooling to 650-750°C at a cooling rate of 1-2°C / min; Preferably, the fourth heat treatment in step (3) includes cooling to 20-30°C at a cooling rate of 0.5-3°C / min.

9. The preparation method according to any one of claims 6-8, characterized in that, In step (4), after the SiO2, Al2O3, B2O3, ZnO, MgO, and CaO are mixed with the second binder, the solid-liquid ratio of the system is 1g:(1-1.5)mL. Preferably, the mixing method in step (4) includes sequential stirring and continuous ball milling, wherein the stirring temperature is 80-90℃ and the time is 2-3h; the continuous ball milling speed is 250-350rpm and the time is 10-12h; Preferably, in the glass glaze slurry of step (4), the solid particles have a Dv50 ≤ 1 μm; Preferably, the fifth heat treatment in step (4) includes heating to 450-500℃ at a heating rate of 1-3℃ / min and holding at that temperature for 0.5-1h; Preferably, the sixth heat treatment in step (4) includes heating to 510-550℃ at a heating rate of 1-2℃ / min and holding at that temperature for 1-2 hours; Preferably, the seventh heat treatment in step (4) includes cooling to 20-30°C at a cooling rate of 0.5-1.5°C / min.

10. An electrical device, characterized in that, Including zinc oxide resistor sheets prepared by the preparation method according to any one of claims 6-9; The electrical equipment includes surge arresters, surge protectors, or new energy converters.